EFFECTS OF ORGANIZATIONAL LEARNING ON PROJECT PERFORMANCE OF CONSTRUCTION FIRMS IN RWANDA, A CASE OF HYGEBAT LTD - Mable Kagarama, Batamuliza (International Journal of Scientific Research and Management (IJSRM), 2021)
Organizational learning is an important function for enhancing project performance because it enables firm’s personnel to acquire and utilize skills and competences through knowledge acquisition, knowledge transformation and knowledge exploitation. This study sought to examine the effects of organizational learning on the project performance in construction firms in Rwanda using the case of Hygebat Ltd. The objectives of the study were to identify the effects of knowledge acquisition analysis, knowledge transformation and knowledge exploitation on the performance of Hygebat Ltd’s construction projects. The researcher used a correlation research design to measure the significance of the relationship between organizational learning and project performance. Data was collected from 54 respondents (5project managers and 49 project staffs) using the close-ended questionnaire and personal interview guide. Respondents were selected by use of stratified and simple random sampling techniques. The validity of research instruments was determined using the content validity index while reliability was verified through the pilot-testing method. Data was analyzed through descriptive (frequency and percentage distribution tables) and inferential statistics (multiple linear regression analysis) and qualitative (use of content analysis). Findings show that all the predictor variables under organizational learning have positive but not statically significant effect on the performance of construction projects in Hygebat Ltd. This is confirmed by the regression coefficients which show that β1=.130(13%), β2=.072(7.2%) and β3=.042 (4.2%) of the positive performance outcomes of Hygebat Ltd’s construction projects are explained by KA, KT and KE respectively. However, the probability values (sig.) of p=.244>0.05 for KA, p=.401>0.05 for KT and p=.682>0.05 for KE show that the effect that organizational learning has on project performance is not statistically significant. Therefore, the research accepts all the null hypotheses (H01, H02 and H03) in explaining the relationship between organizational learning and performance of construction projects in Hygebat Ltd. It is hoped that the study will enable engineers to improve learning and capacity development so that they improve their skills competences and project performance. Other academicians will find the study valuable in benchmarking their studies on the same subject.